Summer and autumn photosynthetic activity in High Arctic biological soil crusts and their winter recovery - Hejduková, Eva; Pushkareva, Ekaterina; Kvíderová, Jana; Becker, Burkhard; Elster, Josef (Frontiers in Microbiology, 2025)
IntroductionBiological soil crusts, found in arid and semi-arid areas worldwide, play a crucial role in the carbon cycle. This study analyzed biocrusts from three different altitudes in Svalbard (High Arctic) in 2022–2024.Methods and resultsMonitoring of microclimatic parameters, including irradiance, humidity, air, and soil temperature, revealed unexpected extremes at the lowest elevation site. Molecular methods were used to determine the diversity of microalgae, revealing the presence of Trebouxiophyceae and Chlorophyceae as the dominant eukaryotic algal groups. Among the cyanobacteria, the dominant taxonomical groups were Nostocales, Pseudanabaenales, and Oscillatoriales. Measured photosynthetic activity was largely driven by irradiance across the different seasons and locations. Higher maximum quantum yield (FV/FM) values (approximately 0.6) were measured at lower irradiance levels (< 100 μmol m−2 s−1). Photosynthetic activity was observed in early October 2022, and diurnal changes were even noticeable at subzero temperatures in late October 2023, with the low irradiance curve being mirrored by the development of FV/FM. Furthermore, thawed biocrusts in winter exhibited the ability to rapidly restore photosynthetic activity, which was also supported by the expression of photosynthesis-related genes. Metatranscriptomic analysis revealed that the differential gene expression observed for the D1, RbcS, Ohp1, and ELIP proteins suggests that light stress-induced photoinhibition plays a major role in biocrusts, particularly in winter.ConclusionThe biocrusts can remain active for extended periods and provide carbon fixation during times when tundra plants primarily engage in respiration, making them very important for the polar environment.